KAJIAN TENTANG ORAL DOCUMENT : TINJAUAN PADA GERAKAN DOKUMENTALIS BARU - Dian Novita Fitriani (Perpustakaan Nasional RI, 2019)
The development of the new concept of documentation is growing so rapidly, breaking the conventional definition of documents that only rely on written texts and printed forms. One development of the concept of document is the oral document developed by Deborah Turner. This study aims to examine the concept of oral document in terms of the concept of the new concept of documentation in the neo Documentum movement. The research method used in this research is qualitative research method with data collection technique through a literature study. The results of this study indicate that the oral document is highly relevant to the development of document definitions in neo-documentary movements that not only focus on the physical form. Documents are more viewed from their function as information providers which provide evidence in various forms so that speech and body language are also included in the concept of documentation.